a. The Triangle Sum Theorem states that the sum of the angles in a triangle is always 180 degrees. So, we can write the equation:
J + K + L = 180
b. Let's substitute the expressions for J, K, and L into the equation:
3x + (12x + 1) + (16x - 7) = 180
Now, let's combine like terms:
3x + 12x + 1 + 16x - 7 = 180
31x - 6 = 180
Next, let's isolate the variable x by adding 6 to both sides of the equation:
31x - 6 + 6 = 180 + 6
31x = 186
Finally, let's solve for x by dividing both sides of the equation by 31:
31x/31 = 186/31
x = 6
So, the value of x is 6.
it shows an image of a triangle.
J =3x
K =(12x+1)
L= (16x-7)
are the angles
a. Write an equation that would help you solve for the missing angle measures. Combine Like Terms! Remember the Triangle Sum Theorem.
b. Solve the equation to find the value of x. Show/Explain all of your steps using inverse operations!
3 answers
Using your value of x from the previous question, solve to find the measure of each angle.(3 points)
m∠J =
m∠K =
m∠L =
m∠J =
m∠K =
m∠L =
We can substitute the value of x (which is 6) into the expressions for each angle to find their measures:
m∠J = 3x
m∠J = 3(6)
m∠J = 18 degrees
m∠K = 12x + 1
m∠K = 12(6) + 1
m∠K = 72 + 1
m∠K = 73 degrees
m∠L = 16x - 7
m∠L = 16(6) - 7
m∠L = 96 - 7
m∠L = 89 degrees
Therefore, the measures of the angles are:
m∠J = 18 degrees
m∠K = 73 degrees
m∠L = 89 degrees
m∠J = 3x
m∠J = 3(6)
m∠J = 18 degrees
m∠K = 12x + 1
m∠K = 12(6) + 1
m∠K = 72 + 1
m∠K = 73 degrees
m∠L = 16x - 7
m∠L = 16(6) - 7
m∠L = 96 - 7
m∠L = 89 degrees
Therefore, the measures of the angles are:
m∠J = 18 degrees
m∠K = 73 degrees
m∠L = 89 degrees